Characterization on insulation performance, poststability, and foaming process of rigid polyurethane sandwich panel for cold storage warehouse - Xu, Jie; Wu, Tao; Sun, Wei; Peng, Chuang (American Society of Civil Engineers, 2017)
Polyurethane (PU) is a commonly used insulation material for cold storage warehouses. The insulation performance of PU sandwich panels made from blended blowing agents were re-assessed by k-factor measurements and insulation thickness calculation based on cold warehouse design standard, which has proved the significant impact of blowing agent difference on energy saving. The foam post-stability was also evaluated by mathematic profiling. The developed 3D paraboloid model based on gridding measurements has provided scientific method for panel shrinkage evaluation. Cell microstructure characterization and post-growth angle coefficients calculation were further performed for better understanding the shrinkage problem at microscopic level. The foaming process model of continuous panel production was developed based on FOAMAT characterization which has provided theoretical solution to panel processing.